Long-term recovery of the human corneal endothelium after toxic injury by benzalkonium chloride. Issue 11 (15th May 2007) - Hughes, E H; Pretorius, M; Eleftheriadis, H; Liu, C S C
Abstract : Introduction: The inadvertent intra-ocular administration of benzalkonium chloride-preserved hydroxypropyl methylcellulose during cataract surgery at another hospital in 1999 resulted in toxic corneal endothelial injury and profound postoperative corneal oedema as a result of endothelial decompensation. The long-term effect of this adverse event was assessed. Methods: All 19 patients were invited to return for examination including corneal endothelial specular microscopy and pachymetry seven years after the incident. Results were compared with data from one year after the incident. Results: Five patients attended for examination, one had received a penetrating keratoplasty and was, therefore, excluded. Ten patients had died and four had moved out of the region and were unable to attend. All four study patients were pain free and achieved 6/12 or better. Mean central corneal thickness reduced by 13% from 652.6 μm at one year to 563.4 μm. Mean central corneal endothelial cell density (n  =  3) increased 28% from 663.7 cells/mm 2 at one year to 835.7 cells/mm 2 (p<0.05). Conclusions: After toxic injury, corneal endothelial function may have a remarkable capacity for recovery even after the first postoperative year. The rise in central endothelial cell density may represent cell migration from less affected areas or cellular proliferation. Should this unfortunate event recur, clinicians may expect continued recovery beyond one year.